2013
DOI: 10.1007/s00248-013-0196-1
|View full text |Cite
|
Sign up to set email alerts
|

N2-Fixation and Seedling Growth Promotion of Lodgepole Pine by Endophytic Paenibacillus polymyxa

Abstract: We inoculated lodgepole pine (Pinus contorta var. latifolia (Dougl.) Engelm.) with Paenibacillus polymyxa P2b-2R, a diazotrophic bacterium previously isolated from internal stem tissue of a naturally regenerating pine seedling to evaluate biological nitrogen fixation and seedling growth promotion by this microorganism. Seedlings generated from pine seed inoculated with strain P2b-2R were grown for up to 13 months in a N-limited soil mix containing 0.7 mM available N labeled as Ca((15)NO3)2 to facilitate detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
63
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 19 publications
10
63
1
Order By: Relevance
“…After a 13-month growth period, pine seedlings treated with P2b-2R were observed to derive most of their foliar N (79%) from BNF (Anand et al, 2013), which was confirmation of the ability of lodgepole pine to fix N after colonization by P. polymyxa. When compared with previous results, we found that inoculated seedlings grown for 7, 9 and 13 months derived 30%, 66% (Bal & Chanway, 2012a) and 79% (Anand et al, 2013), respectively, of their foliar N from the atmosphere.…”
Section: Nitrogen Fixation In Gymnosperms: Effects On Seedling Growthmentioning
confidence: 71%
See 2 more Smart Citations
“…After a 13-month growth period, pine seedlings treated with P2b-2R were observed to derive most of their foliar N (79%) from BNF (Anand et al, 2013), which was confirmation of the ability of lodgepole pine to fix N after colonization by P. polymyxa. When compared with previous results, we found that inoculated seedlings grown for 7, 9 and 13 months derived 30%, 66% (Bal & Chanway, 2012a) and 79% (Anand et al, 2013), respectively, of their foliar N from the atmosphere.…”
Section: Nitrogen Fixation In Gymnosperms: Effects On Seedling Growthmentioning
confidence: 71%
“…The comparatively early onset of BNF and delayed seedling growth response suggest that development of a fully effective N 2 -fixing bacterial population, able to enhance foliar N concentration in pine, is not a rapid process. Establishment of fully effective BNF in pine does not appear to depend on the population size of endophytic diazotrophs because P2b-2R colonization of root, stem and needle tissues in older seedlings did not differ significantly from younger seedlings (Anand et al, 2013), though it is possible that external root colonization was quantitatively related to BNF. However, if BNF is endophytic and requires physiological modifications of bacteria, e.g., differentiation of Paenibacillus into a N 2 -fixing form similar to Rhizobium bacteroids (Postgate, 1998), or plants, e.g., the establishment of specialized sites of BNF within plant tissues or cells, to be fully effective, some time may be required for them to complete.…”
Section: Nitrogen Fixation In Gymnosperms: Effects On Seedling Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Bal et al (2012) successfully isolated several Paenibacillus strains that possess significant acetylene-reduction activity (N-fixing capacity) from the extracts of surface-sterilized lodgepole pine seedling and tree tissues. When one of the strains, P. polymyxa P2b-2R, was re-inoculated in lodgepole pine and grown in an N-limited soil for 13 months, the bacterial strain successfully colonized internal stem and root tissues of lodgepole pine seedlings, fixed a significant amount of N from the atmosphere (79%), and promoted the overall growth of seedlings (Anand et al 2013;Yang et al 2016). Furthermore, a green fluorescent protein-labeled derivative of P2b-2R was shown to colonize internal tissues of lodgepole pine seedlings (Anand and Chanway 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Many paenibacilli are known to act as PGPR in agricultural systems (Anand et al, 2013). Bacteria of this genus are able to colonize diverse habitats like water, soil and insects (Berge et al, 2002;Bosshard et al, 2002;Daane et al, 2002;Peters et al, 2006;Timmusk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%